Peran Jaringan Komunikasi dalam Organisasi Hizbul Whaton Football Club - Arkan, Muhamad Ramzi; Istikhari, Muhammad Ihsan; Ramadhon, Muhammad Rizqullah; Kirana, Mohammad Trydaya (PT Literasi Nusantara Publisher, 2024)
The focus of this article is the role of communication networks in the organization of the Hizbul Wathan Football Club, especially in relation to the field of organization that is carried out, in how to manage the team and organization of the Hizbul Wathan Football Club. The author uses a qualitative method, namely a research method that uses or is based on the philosophy used to research. scientific conditions, in organizational communication anyone can speak or communicate to influence or provide input in order to achieve the goals agreed at the beginning or resolve problems that exist within the Hizbul Wathan Football Club organization.